TLR4 Associated Signaling Disrupters as a New Means to Overcome HERV-W Envelope-Mediated Myelination Deficits - Göttle, Peter; Schichel, Kira; Reiche, Laura; Werner, Luisa; Zink, Annika; Prigione, Alessandro; Küry, Patrick (Frontiers in Cellular Neuroscience, 2021)
Myelin repair in the adult central nervous system (CNS) is driven by successful differentiation of resident oligodendroglial precursor cells (OPCs) and thus constitutes a neuroregenerative process capable to compensate for functional deficits upon loss of oligodendrocytes and myelin sheaths as it is observed in multiple sclerosis (MS). The human endogenous retrovirus type W (HERV-W) represents a MS specific pathogenic entity and its envelope (ENV) protein was previously identified as negative regulator of OPC maturation – hence of relevance in the context of diminished myelin repair. We here focused on the activity of the ENV protein and investigated how it can be neutralized for an improved remyelination. ENV mediated activation of TLR4 increases inducible nitric oxide synthase (iNOS) expression, prompts nitrosative stress and results in myelin-associated deficits including decreased levels of oligodendroglial maturation marker expression and morphological alterations. Intervention of TLR4 surface expression represents a potential means to rescue such ENV dependent deficits. To this end, the rescue capacity of specific substances, either modulating V-ATPase activity or myeloid differentiation 2 (MD2) mediated TLR4 glycosylation status, such as compound 20 (C20), L48H437 or folimycin were analyzed, as these processes were demonstrated to be relevant for TLR4 surface expression. We found that pharmacological treatment can rescue the maturation arrest of oligodendroglial cells and their myelination capacity, and can prevent iNOS induction in the presence of the ENV protein. In addition, downregulation of TLR4 surface expression was observed. Furthermore, mitochondrial integrity crucial for oligodendroglial cell differentiation was affected in the presence of ENV and ameliorated upon pharmacological treatment. Our study therefore provides novel insights into possible means to overcome myelination deficits associated with HERV-W ENV mediated myelin deficits.